Literasi Keuangan dan Penggunaan Pembayaran Digital pada UMKM di Indonesia - Rio Adika Putra; Muslimin Muslimin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Financial literacy plays an important role in supporting the ability of Micro, Small, and Medium Enterprises to adapt to the development of digital payments in Indonesia. The increasing use of QRIS, e-wallets, mobile banking, and technology-based payment services requires MSME actors to understand the benefits, risks, and proper use of digital financial services. This study aims to examine the role of financial literacy in the use of digital payments among MSMEs in Indonesia, including supporting factors, obstacles, and implications for strengthening MSME digitalization. This research uses a descriptive qualitative approach with a systematic literature study method. The data were obtained from 13 scientific articles indexed in nationally accredited journals at least Sinta 4, published between 2021 and 2026, and supported by official documents from relevant authorities. The findings show that financial literacy plays a role in increasing the readiness, trust, and decisions of MSME actors to use digital payments. However, low financial literacy, perceived risk, limited infrastructure, and conventional transaction habits remain obstacles to digital payment adoption. The implications of this study indicate the need for inclusive digital financial education, continuous assistance, and collaboration among the government, regulators, financial institutions, and fintech providers in strengthening the digital transformation of MSMEs.